IMPROVING THE ABILITY TO WRITE Fiction PROSA (SHORT STORY) USING INTERACTIVE LEARNING MEDIA SEMESTER 7A PBSI UNIVERSITY OF MUSLIM NUSANTARA AL WASHLIYAH YEAR 2020/2021 - Fita Fatria; Putri Juwita; Tiflatul Husna (SENSEI RESEARCH CENTER, 2021)
This study aims to determine the ability to write prose fiction and drama by applying the use of video-based interactive learning media in the 7 semester of PBSI, University of Muslim Nusantara Al Washliyah year 2020/2021. The research method used in this research is quantitative descriptive method using Classroom Action Research (CAR). The population in the study amounted to 91 in 7 semester students of the PBSI Department at the Muslim Nusantara Al-Washliyah University. The sample in this study was 32 students in semester 7A PBSI University of Muslim Nusantara Al Washliyah year 2020/2021. Before carrying out cycle I, the initial test obtained an average score of 66.9, or the percentage of outcome assessment (PPH) of 66.9%. The next step is to carry out the action with II cycles. In cycle II, the average score of 72.4, or the percentage of outcome assessment (PPH) of 72.4%, is higher than the initial test, but has not met the target of implementing the action. To achieve better learning, reflection is carried out for further action. Then proceed to cycle II with an average value of 80.4, or the percentage of outcome assessment (PPH) of 80.4%. The target for the implementation of the measures was an average of 70 individually and classically. This means that there is a very significant increase